Survey of second‐trimester maternal serum screening in Japan. Issue 5 (20th March 2013) - Okuyama, Torayuki; Yotsumoto, Junko; Funato, Yumi
Abstract Aim Second‐trimester maternal serum screening (MSS) is the predominant form of prenatal screening in Japan. We hypothesize that patient education and physician knowledge of Down syndrome (DS) screening are insufficient to provide adequate information regarding prenatal screening in Japan. Material and Methods In‐person or telephone interviews with medical personnel were conducted at 25 medical facilities utilizing Afp4 (Esoterix Genetic Laboratories, LLC, a wholly‐owned subsidiary of Laboratory Corporation of America Holdings) second trimester screening. We explored how medical facilities provided information about the MSS process to pregnant women. Results Before prenatal testing, 60% of medical facilities spent an average of less than 5 min per patient explaining the MSS process. The option of amniocentesis for chromosomal aneuploidy was explained at nearly all facilities, but only 60% explained the risk of amniocentesis. Ultrasound examination for open neural tube defects was explained only at half the facilities. Only five of 25 (20%) medical practitioners explained the possibility of having congenital disorders fetus. Conclusion This study revealed that most obstetricians in Japan do not provide their patients with sufficient information about MSS.